2011
DOI: 10.1017/s1743921312010782
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing surveys for close binary central stars and wider implications

Abstract: Abstract. Binary central stars have long been invoked to explain the vexing shapes of planetary nebulae (PNe) despite there being scant direct evidence to support this hypothesis. Modern large-scale surveys and improved observing strategies have allowed us to significantly boost the number of known close binary central stars and estimate at least 20% of PNe have close binary nuclei that passed through a common-envelope (CE) phase. The larger sample of post-CE nebulae appears to have a high proportion of bipola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…The binary scenario has been explored both theoretically (e.g., Soker & Rappaport 2001) and observationally (e.g., Miszalski 2012;Boffin et al 2012), and while it can explain a number of structures observed in the nebulae, it is unlike gravitational interactions are sufficient to explain all the variety of outflows found in the same nebula (see e.g., the case of Mz3 in Santander et al 2004, where four distinct flows with increasing collimation degree have been identified).…”
Section: Introductionmentioning
confidence: 99%
“…The binary scenario has been explored both theoretically (e.g., Soker & Rappaport 2001) and observationally (e.g., Miszalski 2012;Boffin et al 2012), and while it can explain a number of structures observed in the nebulae, it is unlike gravitational interactions are sufficient to explain all the variety of outflows found in the same nebula (see e.g., the case of Mz3 in Santander et al 2004, where four distinct flows with increasing collimation degree have been identified).…”
Section: Introductionmentioning
confidence: 99%